Karakteristik Parsial Gen Sitokrom-C Oksidase Subunit-I Katak Pohon Suaka Marga Satwa Tanjung Peropa Moramo, Sulawesi Tenggara (CHARACTERISTICS OF PARTIAL CYTOCHROME C OXIDASE SUBUNIT I (COI) GENE OF TREE FROG (Polypedates celebensis) IN TANJUNG PEROPA WI - Suriana, Suriana; Nasaruddin, Nasaruddin (Jurnal Veteriner, 2017)
Tree frog (Polypedates celebensis) is an endemic amphibi found in Southeast Sulawesi. Database ofthis species, in particular genetic databases is still very limited. The purpose of this research was tocharacterize the partial gene cytochrome C oxidase subunit I (COI) of tree frog (P. celebensis). Frog sampleswere collected from Tanjung Peropa Wildlife Reserve, Moramo, Southeast Sulawesi, and extracted theirDNA genome, and amplified using the polymerase chain reaction (PCR) method, with specific primers,and then sequenced. Characterization was done by comparing the COI gene with another COI gene fromother frog (data available on GenBank). The results showed that the COI gene fragment P. celebensisconsisted of 665 base pairs. These fragment gene had 99% conserved nucleotides, and only 1% nucleotidesthat varied. Nine sites of nucleotide varied namely: 65th, 98th, 101th, 358th, 396th, 403th, 405th, 424th, and426th. These sites of nucleotide varied can be used as genetic markers for P. celebensis. Composition ofnitrogenous bases P. celebensis COI gene fragment were 29.9% timine, 28.9% cytocine, 22.0% adenine, and19.2% guanine. Molecular phylogeny of P. celebensis based on 665 bp of their COI gene suggests that thesespecies was monophyletic. It is concluded that the gene fragment of cytochrome C oxidase of tree frog (P.celebensis) the origin of Wildlife Moramo, Southeast Sulawesi, has conserved nucleotides more thannucleotides that varied. These varied nucleotides can be used as genetic markers especially for the treefrog origin of Wildlife Moramo, Southeast Sulawesi. The most nitrogenous bases is thymine, while thefewest is guanine. Molecular phylogeny based on cytochrome C oxidase gene is monophyletic
Keywords: cytochrome C oxidase subunit I gene; Polypedates celebensis; genetic markers